Efektivitas Pengelolaan Kelas di Madrasah Tsanawiyah Negeri 2 Padang Lawas Utara - Harahap, Saimarlina; Purnamasari, Editha Dewi; Hafni, Syafrida (Permata : Jurnal Pendidikan Agama Islam, 2024)
This research aims to contemporize exploratively the function of school supervisors through juridical functions for the Effectiveness of Classroom Management in Madrasah Tsanawiyah Negeri 2 Padang Lawas Utara This research was conducted Madrasah Tsanawiyah Negeri 2 Padang Lawas Utaratahun 2022-2023 This school is located in Padang Lawas Utara, North Sumatra Province, Indonesia. The type of research applied is qualitative research. The qualitative research approach used is exploratory qualitative research. The results of this study indicate that the effectiveness of classroom management in Madrasah Tsanawiyah Negeri 2 Padang Lawas Utara has not been managed properly and correctly. This can be seen from the Islamic Religious Education teacher in applying skills related to the principles of using classroom management. Islamic Religious Education teachers who enter class VII-3 of Madrasah Tsanawiyah Negeri 2 Padang Lawas Utara only apply the principles of warmth and enthusiasm, challenge, emphasis on positive things and instilling self-discipline. And the principles of variety and flexibility have not been applied in classroom management. Then the ability of PAI teachers to apply skills related to creating and maintaining optimal learning conditions has not all been applied. Islamic Religious Education teachers who enter class VII-3 of Madrasah Tsanawiyah Negeri 2 Padang Lawas Utara only apply the components of dividing attention and focusing group attention. Furthermore, the component of being responsive has not been applied in classroom management.Keyword : Effectiveness; Classroom Management; Madrasah Tsanawiyah